3, 4-Dihydroxyphenethyl nitrate with nitric oxide releasing, antioxidant, hypoglycemic and hypolipidemic effects. Issue 15 (1st August 2020) - Xie, Yun-Dong; Liu, Ji-Ping; Wang, Wei; Shi, Yong-Heng; Wang, Xiao-Ping; Sun, Meng; Xu, Xin-Ya; Li, Na
Graphical abstract: Highlights: HT-ONO2 was designed, synthesized and evaluated. HT-ONO2 exhibited NO releasing, antioxidant, α-glucosidase inhibition and vasodilation activity in vitro . HT-ONO2 displayed hypoglycemic, hypolipidemic, antioxidant and NO supplement in vivo . Abstract: Nitric oxide (NO) dysfunction, oxidative stress, and dyslipidemia are main risk factors associated with the pathophysiology of diabetic complications. In this study, 3, 4-dihydroxyphenethyl nitrate (HT-ONO2 ) was designed, synthesized and evaluated, which incorporated hydroxytyrosol (HT) and nitrate. HT-ONO2 significantly exhibited hypoglycemic activity after oral administration to diabetic mice induced by streptozocin (STZ). HT-ONO2 also potently decreased plasma triglyceride (TG), total cholesterol (TC) in hyperlipidemia mice induced by Triton WR 1339. Meanwhile, HT-ONO2 displayed NO-releasing and antioxidant activity both in diabetic and hyperlipidemia mice and in vitro . Moreover, HT-ONO2 shown definite vasodilation and α-glucosidase inhibition activity in vitro . The results suggested that the hybrid hydroxytyrosol-based nitrate with NO supplement, antioxidant, hypoglycemia and hypolipidemia provided a potential multi-target agent to ameliorate the diabetes mellitus and its complications.